Prevalence of Metabolic Syndrome and its Determinants in Tirunelveli City Police (International Journal of Physiology, 2020)
Introduction: Metabolic syndrome has been reported to be on the rise in general population, more so inpersonnel involved in occupational stress. Hence the present study is undertaken to find out the prevalenceof metabolic syndrome and to determine the factors associated with it among the police personnel inTirunelveli city.Method: This is a cross-sectional study in which 133 police personnel working in Tirunelveli city in theage group of 30-58 were included. After getting due permission from the Deputy Commissioner of PoliceTirunelveli city, Head of Department of Bio chemistry, Institutional Ethical Committee clearance and oralinformed consent from the volunteers, the study was started. The study was conducted during the period ofAugust, 2013. Analysis was done using Chi square test and t test using SPSS software version 16. Results:Among the 133 police personnel examined, 92 of them were identified with metabolic syndrome. Hence,prevalence was found to be 69.1%. Majority of them 26 (28.3%) fell in the age group of 41 to 45 years.History of Smoking, Hypertension and Diabetes were found to be higher among those with metabolicsyndrome (31.5%, 20.7% and 17.4%) as compared to those who were not affected (7.3%, 7.8% and 2.4%)and they were found to be statistically significant with P values of 0.003, 0.007 and 0.017 respectively. Themean values of Age, BMI, Waist circumference, Systolic BP, Diastolic BP, Mean Arterial BP, Fasting BloodSugar, Serum Triglycerides and VLDL were significantly higher among those who were having metabolicsyndrome as compared to other participants.